Analysis of thermal transport and entropy generation characteristics for electroosmotic flow through a hydrophobic microchannel considering viscoelectric effect. (October 2021) - Pabi, Souvik; Mehta, Sumit Kumar; Pati, Sukumar
Abstract: We investigate the thermo-fluidic and entropy generation characteristics for electroosmotic flow through a hydrophobic microchannel with the consideration of viscoelectric effect. A closed form expression for the velocity is obtained from the analytical solution of the momentum and continuity equations together with the Poisson-Boltzmann equation and thereafter the temperature field is computed numerically. The flow velocity, flow rate, average Nusselt number, and average total entropy generation are computed by varying the slip coefficient, viscoelectric coefficient ( f ), Brinkman number ( Br ), and thermal Peclet number( Pe ). Results reveal that the viscoelectric effect decreases the flow velocity and percentage decrement in flow rate due to the viscoelectric effect is larger for the slip case and reaches up to 40.09%. The value of the average Nusselt number decreases with f at lower value of Br, and the effect is opposite at higher values of Br . Although the heat transfer enhancement is more with the interfacial slip, the augmentation decreases with f and increases with Pe . The value of average total entropy generation decreases with the increase in f, and decrement is substantial at higher values of Br .